Analisis Tingkat Kerusakan Jalan dengan Menggunakan Metode Pavement Condition Index (PCI) (Studi Kasus : Jalan P. Tirtayasa Bandar Lampung) - Zaid, Muhammad; Sulistyorini, Rahayu; Ofrial, Siti Anugrah Mulya Putri (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
The purpose of this study is to explain the types of damage to the flexible pavement surface layer, to determine the index value of the pavement condition on the P. Tirtayasa road section based on the PCI (Pavement Condition Index) method, so that these results can be used in the preparation of road maintenance programs. The results of this study are the average of Pavement Condition Index (PCI) value on P. Tirtayasa street is 49.4 with moderate conditions (fair). The most dominant type of damage was patches with a damaged area of 2378.96 m (44.7%), then crocodile cracks with a damaged area of 1375.01 m (25.8%). Judging from the damage to the existing roads, it is necessary to patch, cover cracks, fill cracks, pave and smooth the roads for the damage that has occurred and then overlay and continue with a routine maintenance program. Keywords: road damage, PCI method, road maintenance.